NOŻE WOLUTOWE – O FUNKCJI I POCHODZENIU ZAGADKOWYCH PRZEDMIOTÓW W KULTURZE SŁOWIAŃSKIEJ - Pawlicki, Jakub Karol (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2021)
The text presents spiral knives, objects of clearly exceptional nature. The data, the map and table included here are meant to update information on the subject after 32 years. Identification of the specific regional groups and a metric analysis of the historical objects highlight the differences between the groups. The text also touches upon objects which are morphologically close to the spiral knives used by nomadic communities. A critical look at the theories in literature on the subject allowed to limit the functions to two, possibly mutually complementary.